2014
DOI: 10.1038/srep04621
|View full text |Cite
|
Sign up to set email alerts
|

The optimal concentration of topical hydroxycamptothecin in preventing intraarticular scar adhesion

Abstract: 10-Hydroxycamptothecin could reduce intraarticular adhesion by inhibiting fibroblasts proliferation after knee surgery. However, the ideal concentration of hydroxycamptothecin have not been defined. This study was tried to verify the optimal concentration of 10-hydroxycamptothecin in preventing knee intraarticular adhesion. Sixty rabbits were randomly divided into five groups. Approximately 10 mm × 10 mm of the cortical bone was removed from both sides of the femoral condyle and the underneath cancellous bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Owing to the anti‐fibrotic effect of anti‐tumor drugs, positive results have been achieved in reducing post‐operative skeletal fibrosis. Previous studies have shown that topical application of anti‐tumor drugs, including mitomycin C (MMC), 10‐hydroxycamptothecine (HCPT), colchicine and 5‐fluorouracil (5‐Fu), could prevent post‐operative skeletal fibrosis in animal models by inhibiting the inflammatory response, suppressing fibroblast proliferation and reducing collagen deposition. However, more research is needed to determine the exact effect of 5‐Fu .…”
Section: Current Therapies For Post‐operative Skeletal Fibrosismentioning
confidence: 99%
“…Owing to the anti‐fibrotic effect of anti‐tumor drugs, positive results have been achieved in reducing post‐operative skeletal fibrosis. Previous studies have shown that topical application of anti‐tumor drugs, including mitomycin C (MMC), 10‐hydroxycamptothecine (HCPT), colchicine and 5‐fluorouracil (5‐Fu), could prevent post‐operative skeletal fibrosis in animal models by inhibiting the inflammatory response, suppressing fibroblast proliferation and reducing collagen deposition. However, more research is needed to determine the exact effect of 5‐Fu .…”
Section: Current Therapies For Post‐operative Skeletal Fibrosismentioning
confidence: 99%
“…Extracellular matrix proteins, such as collagen, are produced by fibroblasts. In joint injury-induced contracture, inhibiting fibroblast proliferation by anti-proliferative agents MMC or hydroxycamptothecin can attenuate fibrosis in intraarticular adhesion sites (Li et al 2013b, Liang et al 2014. Therefore, it seems likely that fibroblast proliferation plays an important role in generating joint fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The rabbit knee intra-articular adhesion model was performed according to the previous protocol [ 3 ]. Sterile conditions were prepared beforehand.…”
Section: Methodsmentioning
confidence: 99%
“…Selecting 3 rabbits randomly per group, macroscopic evaluation was performed 4 weeks post-surgery. The surgical knee was reopened with re-anesthesia, and the presence and severity of intra-articular adhesions was evaluated, with the results based on the visual scoring system ( Table 1 ) [ 1 3 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation